Modelling automated data manipulation and record management to improve internal examination operation: a case study in FTMSK / Azlan Ismail, Mohamad Norzamani Sahroni and Marina Ahmad - Ismail, Azlan; Sahroni, Mohamad Norzamani; Ahmad, Marina (2006)
Faculty of Information Technology and Quantitative Science implemented its internal examination according to specific processes governed by the requirements outlined by UiTM and the ISO guidelines. There are several critical situations whereby certain processes require accurate data from its previous processes. There are also some problems encountered in the current practice such as copy and paste method, no database, data redundancy and more. Thus this research will design and develop a web-base system to manage data as centralized management and producing efficient report for internal exam operation of FTMSK. The system is designed using Unified Modeling Language (UML) and prototyping is selected as the methodology. The system is developed using PHP programming language and it runs on apache web server. MySQL is used as its database server. The target of this project is to produce a prototype of an automated data manipulation and record management system for internal exam operation of FTMSK.